Mutu Glikemik Kue Bingke Variasi Umbi di Kota Pontianak - Lestari, Oke Anandika; Dewi, Yohana Sutiknyawati Kusuma; Putri, Mardiana (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2020)
This study aims to obtain the number of consumption portions (g) of sweet potato and potato variations of bingke which have a low glycemic load (GL) value. GL is the glycemic load of a food after being consumed at a certain amount. The GL value is determined from the glycemic index (GI) value and the carbohydrate content per serving. The glycemic index is food categorization (low, medium, high) based on its speed in increasing glucose levels in the blood. Diabetes mellitus sufferers are advised to pay attention to food consumption based on food categories, especially those with low GI values. However, the amount consumed will also affect the increase in glucose levels in the blood, this is reflected in the GL value. This study was conducted using 10 healthy respondents aged 22 years, normal body mass index (BMI), normal fasting blood sugar, and not smoking. The results obtained by the variety of tuber bingke cakes (sweet potatoes and potatoes) have a high GI value category with a low GL consumption portion of 120 g (2 pieces). As a complement to the data, a survey was also carried out on 100 random respondents which showed that the type of bingke cake the variety of sweet potato was preferred and the number of consumption of one meal of bingke cake was two pieces.This amount can be recommended to be the amount of one consumption (one meal portion).